2020
DOI: 10.3390/ani10020225
|View full text |Cite
|
Sign up to set email alerts
|

Partial Substitution of Fermented Soybean Meal for Soybean Meal Influences the Carcass Traits and Meat Quality of Broiler Chickens

Abstract: The usage of fermented soybean meal (FSBM) in poultry feed is limited due to the high cost. The present study was conducted to examine the carcass traits and meat quality of broiler chickens that were fed diets with partial replacement of soybean meal (SBM) with FSBM. The 336 one-day-old chicks were assigned to four groups with 0% (control), 2.5%, 5.0%, and 7.5% FSBM addition in corn-SBM-based diets. Compared with the control, 2.5% and 5.0% FSBM decreased leg muscle yield, breast drip loss, and cooking loss (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
(48 reference statements)
3
27
0
2
Order By: Relevance
“…Similarly, fermented barley or wheat had more potent DPPH radical scavenging activities than the control diet (107). Moreover, the antioxidant function of fermented soybean meal might be derived from its fermentation products by reduced breast hydrogen peroxide level (108). It was described that during the microbial fermentation of soybean meal with Bacillus amyloliquefaciens, the antioxidant compounds, such as the phenolic and flavonoid compounds, increased sharply and the administration of lyophilized FSBM supernatant enhanced the T-SOD, glutathione peroxidase, catalase activities, and total antioxidant capacity and inhibited MDA formation in the serum and liver of mice (109).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, fermented barley or wheat had more potent DPPH radical scavenging activities than the control diet (107). Moreover, the antioxidant function of fermented soybean meal might be derived from its fermentation products by reduced breast hydrogen peroxide level (108). It was described that during the microbial fermentation of soybean meal with Bacillus amyloliquefaciens, the antioxidant compounds, such as the phenolic and flavonoid compounds, increased sharply and the administration of lyophilized FSBM supernatant enhanced the T-SOD, glutathione peroxidase, catalase activities, and total antioxidant capacity and inhibited MDA formation in the serum and liver of mice (109).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Kim et al [ 36 ] also reported that dietary supplementation with 3% FSBM products during the first seven days after hatching did not affect the relative weights of both breast muscle and abdominal fat at 35 days. Guo et al [ 37 ] found that fermented SBM had no effect on the breast muscle index and abdominal fat yield of broilers. Moreover, partial substitution of FSBM for SBM (4.5%–6.0%) did not change the weight and relative weight of the abdominal fat in broiler chickens at 37 days [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Palma et al [ 19 ] addressed that a discrepant diet can affect the nutrient deposition in skeletal muscle by modifying the gastrointestinal microbiome and metabolome of sheep. Guo et al [ 20 ] found that partial substitution of FSM for soybean meal in broilers’ diet improved the carcass yield and meat quality of broiler chickens. Thus, types of fermented feed can differentially impact the growth performance and meat quality of lambs.…”
Section: Discussionmentioning
confidence: 99%